2020
DOI: 10.1080/23311916.2020.1762523
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and practice of metal industries into global supply chain integration: A literature review

Abstract: The objective of this study was to investigate the current research practices and existing progress research published on supply chain management and supply chain integration in an attempt to provide a research agenda for future investigations. Mainly the secondary data analysis and methods employed for the investigations. Particularly a systematic literature review analysis from 115 papers published from 16 important journals in the supply chain, logistics, Industrial management & data systems, supply chain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Other study conducted by Dametew et al (2020) developed a conceptual model by integrating TQM, JIT and SCM initiatives. In this study, the authors primarily assessed and investigated the challenges and trends of global competitiveness of basic metal industries.…”
Section: Existing Integrated Kaizen Philosophy Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…Other study conducted by Dametew et al (2020) developed a conceptual model by integrating TQM, JIT and SCM initiatives. In this study, the authors primarily assessed and investigated the challenges and trends of global competitiveness of basic metal industries.…”
Section: Existing Integrated Kaizen Philosophy Frameworkmentioning
confidence: 99%
“…Thus, this research will provide an associated result by identifying the most widely found practices of the stated CI programs in literatures. For this case, these most extensively quoted practices of the programs can be divided into unique techniques or practices to all programs separately, and drivers (or social and technical factors or common practices or CSFs) to all the programs as used in (Lopes et al, 2022;Sisay et al, 2021;Dametew et al, 2020;Sahoo and Yadav, 2020;Tilahun et al, 2020;Phan et al, 2019;Hailu et al, 2018a;Masudin and Kamara, 2018;Khamkham, 2017;Tesfaye and Kitaw, 2017;Getachew et al, 2017;Dametew et al, 2017;Nandurkar et al, 2014;Cua et al, 2001).…”
Section: Existing Integrated Kaizen Philosophy Frameworkmentioning
confidence: 99%
See 3 more Smart Citations